Banking crises, liquidity, and credit lines : a macroeconomic perspective - Singh, Gurbachan (London ; New York : Routledge, 2012)
The banking crisis in 2007-10 was one amongst many such crises in the past. This book provides a fresh approach to liquidity. It starts from basics and gradually builds up analysis of credit lines with few technicalities. Though the analysis is theoretical, the book provides a historical background, a macroeconomic perspective, and policy implications. An integrated view of the pre-1983 and the post-1983 literature is provided. A solution to the related problem of sudden outflow of funds from emerging economies is also suggested.
Includes bibliographical references and index.
oif 17/04/14
Loan
Keywords: Bank liquidity; Lines of credit; Financial crises